2015
DOI: 10.1038/pr.2015.247
|View full text |Cite
|
Sign up to set email alerts
|

Inherited disorders of bilirubin clearance

Abstract: Inherited disorders of hyperbilirubinemia may be caused by increased bilirubin production or decreased bilirubin clearance. Reduced hepatic bilirubin clearance can be due to defective 1) unconjugated bilirubin uptake and intrahepatic storage, 2) conjugation of glucuronic acid to bilirubin (e.g. Gilbert syndrome, Crigler-Najjar syndrome, Lucey-Driscoll syndrome, breast milk jaundice), 3) bilirubin excretion into bile (Dubin-Johnson syndrome), or 4) conjugated bilirubin re-uptake (Rotor syndrome). In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(148 citation statements)
references
References 76 publications
5
131
0
12
Order By: Relevance
“…We found that glucuronic acid levels were significantly reduced in patients with cirrhosis, which directly affected the metabolism of bilirubin. This finding was consistent with the exacerbation of jaundice concurrent with the reduction of hepatic compensatory ability [36]. …”
Section: Discussionsupporting
confidence: 85%
“…We found that glucuronic acid levels were significantly reduced in patients with cirrhosis, which directly affected the metabolism of bilirubin. This finding was consistent with the exacerbation of jaundice concurrent with the reduction of hepatic compensatory ability [36]. …”
Section: Discussionsupporting
confidence: 85%
“…The mutation, A (TA) 7TAA, is thought to be the main cause of the syndrome in Caucasians; however, more than 100 different mutations have been implicated in GS, including enhancer polymorphisms that lower transcriptional activity, as well as missense mutations which affect enzyme function 9.…”
Section: Commentarymentioning
confidence: 99%
“…Отмена ГВ на короткое время показана в исключительных случаях [7,24]. Таким образом, желтуха грудного молока вызвана сочетанием генетических и экологических факторов (например, компонентов груд-ного молока) [25]. Желтуха, связанная с ГВ (ЖГВ), точнее с недостаточным ГВ, обусловлена, кроме сниженной конъюгации билирубина, еще и повышенной энтерогепа-тической циркуляцией билирубина, которая возникает при голодании [26].…”
Section: Arias Et Al (1963) [11] и Newman Et Al (1963)unclassified